2020
DOI: 10.1177/0022034520957233
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Dementia: A Critical Examination

Abstract: Dementia is a major contributor to dependence and disability in older people, with aging societies characterized by growing numbers of people living with the condition. Dementia rates are highest in those with low education early in life, midlife hypertension, midlife hearing loss, depression, obesity, loneliness, a sedentary lifestyle, or sustained exposure to smoking or diabetes. Tooth loss is a putative risk factor for dementia which has received increasing research attention, but systematic review findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 42 publications
1
82
1
Order By: Relevance
“…(2) an indirect process via inflammatory mediators; and (3) the induction of the expression of platelet aggregation proteins [46]. One of two recent reviews concluded that chronic periodontitis resulting in tooth loss, but not before the inflammation, has affected the central nervous system by impairing cognition [47]. The other review indicated that the causal relationship between periodontitis and Alzheimer´s disease is unknown [48].…”
Section: Discussionmentioning
confidence: 99%
“…(2) an indirect process via inflammatory mediators; and (3) the induction of the expression of platelet aggregation proteins [46]. One of two recent reviews concluded that chronic periodontitis resulting in tooth loss, but not before the inflammation, has affected the central nervous system by impairing cognition [47]. The other review indicated that the causal relationship between periodontitis and Alzheimer´s disease is unknown [48].…”
Section: Discussionmentioning
confidence: 99%
“…Thomson and Barack [ 40 ] suggested that the possible related mechanisms between tooth loss and cognitive decline in older people are: (1) Tooth loss can compromise nutritional status and this can lead to a weakened nervous system. (2) Tooth loss results in less “interoclusal contacts”, therefore, less somatosensory feedback, leading to a cognitive decline, and (3) chronic periodontitis drives tooth loss, and during this inflammatory process, CNS can be affected, as so can cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The oral health and hygiene of older people with dementia need to be improved [ 40 , 41 , 42 ]. This could be achieved through caregiver education in oral health, the use of oral disease detection tools, the assistance of dental professionals in adequate oral care and correct treatment planning, behavioral management of dementia patients, and the intervention of multidisciplinary health professional teams [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one should also consider the person’s ability to adapt mastication to changes in dental status [ 45 ] and whether this is impaired in AD/ARD. Currently, evidence supporting the association between tooth loss, masticatory performance, and dementia is still lacking [ 46 , 47 ]. (2) AD and oromotor dysfunctions share common risk factors : aging, diet/nutrition, and socio-economic status [ 7 ].…”
Section: The Link Between Age-related Oromotor Dysfunction and Admentioning
confidence: 99%